Tingkat Persepsi Siswa Terhadap Kehadiran Teman Sebaya dengan Kecenderungan Kepribadian Narsistik Pada SMK di DIY - Viola Puspa Kirana; Taufik Agung Pranowo (Scidacplus, 2026)
This research is motivated by the importance of understanding students' perceptions of the presence of peers who have narcissistic personality tendencies because it can affect interpersonal relationships and social dynamics in the school environment. This study aims to determine the level of narcissistic personality tendency in peers and describe students' perceptions of the presence of peers with narcissistic personality tendencies in vocational schools in the Special Region of Yogyakarta (DIY). The research hypothesis states that students' perception of the presence of peers with narcissistic personality tendencies is in the medium category. The research uses a quantitative approach with a descriptive method. The research sample amounted to 436 vocational school students in DIY who were selected using the cluster random sampling technique. Data collection was carried out using the student perception scale and analyzed with descriptive statistics. The results showed that students' perception of the presence of peers with narcissistic personality tendencies was dominated by the medium category, namely 346 students (79.36%), the high category as many as 78 students (17.89%), and the low category as many as 12 students (2.75%). These findings suggest that most students have a fairly objective perception of peers with narcissistic personality tendencies. The results of the research are expected to be the basis for Guidance and Counseling teachers in designing services to improve empathy, social acceptance, and healthy interpersonal relationships in schools.